Alien seed beetles (Coleoptera: Chrysomelidae: Bruchinae) in Europe - Yus-Ramos, Rafael; Ventura, Daniel; Bensusan, Keith; Coello-García, Pedro; György, Zoltán; Stojanova, Anelia (Zootaxa, 2014)
Under the framework of the DAISIE consortium, whose main mission is to make an inventory of the alien invasive species of Europe and its islands, we review the current state of knowledge and provide an up-to-date catalogue and distributional status for alien seed beetles (Coleoptera: Chrysomelidae: Bruchinae) in Europe. This work is based on studies of the species detected from the last century to the present, but with greater emphasis on the beginning of the 21st century, during which new biological studies have been carried out and findings made in European countries. The main objective of this paper is to focus on this last fact, which has promoted new views on the existing and potential threat of exotic bruchids in relation to climate change. This must now be regarded as a matter of concern for European agricultural and environmental policies. Only species of exotic origin introduced in European regions outside their native range were considered. Therefore, species of European origin spreading to new countries within Europe are not treated. Also, we provide a new approach to classifying alien seed beetle species according to their ability to become established, distinguishing between the well-established and those that may appear in seed stores but are not capable of invading natural and agricultural ecosystems. We present a taxonomic characterization of the alien bruchids found in Europe, providing an illustrated key based on external morphological characters of adults. The key facilitates the identification of the sixteen most frequently recorded genera, which represent 37 of the 42 species of exotic species recorded in Europe up to the present, whether established, not established or occasional. Finally, we provide a summary of the state of knowledge of the taxonomy and biology of the 20 most worrying species as pests, both established and non-established. This includes, where appropriate, an illustrated key for the identification of species. The study reveals that the majority of exotic bruchid species in Europe originate in Asia and Africa, from host plant species imported for ornamental or forestry purposes, and that a greater effort in European customs control is advisable.